The moderating effect of organizational changes on the influence of ethical decision making on public sector internal auditor performance - Souha Bouaziz Siala; Anis Jarboui (Contemporary Economics, 2019)
This study investigates the role of organizational change in moderating the effect of ethical decision making on internal auditor performance. The study population comprises internal auditors who work in the public sector (a government-owned company in Indonesia). Smart Partial Least Square statistic software is used to test the hypotheses. This study has led to three findings. First, this study finds that ethical decision making provides support for auditor performance. Second, this study finds that organizational change does not provide support for auditor performance. Third, the analysis shows that the role of organizational change does not succeed in helping to strengthen or weaken ethical decision making in auditor performance.
Keywords: M42; M48; H83; L2; 330; Organizational changes; Ethical decision making; Internal auditor performance; Public sector